Järnvägsstationerna och deras omgivning : då och nu med fyra exempelstationer - Sandberg, Victoria (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2020)
Since the nineteenth century the railway stations have been a part of the Swedish transport network. Some of the stations have been closed since the car made it´s way into society. In recent years some stations have reopened and new once have been built. The view on traveling has changed quite a bit since the arrival of trains and what is important at a railway station has shifted. In this paper four stations have been examined through literature study of papers from the municipalities and Trafikverket (The Swedish Transport Government). Visits at the sites have been made for the purpose of discovering any differences between the stations from the nineteenth century and those built today, together with any new trends that might be visible at the drawings of the sites. This has been complemented with a literature study of the history of the Swedish railway, parks and squares. The results of the investigation shows that the ideas of today had been implemented on the sites of the older stations to some extent but significantly more so at the newly built stations. The largest changes where that the stations had become more of a central for travels with the possibility of exchange between different ways of transport; train, bus, car and bike, rather than merely train stations. But the trends have as well been changing towards the past with more vegetation and less parking spaces for cars, although more parking for bikes. The square as a meeting place is still there but it is more significant that there is a space for meeting rather than that it has to be an actual square. Finally, the investigation came to the conclusion of that there are multiple elements that is seen as self-spoken and important, but that this is slowly changing with the development of the society.